PENERAPAN PENDIDIKAN HUKUM PADA SISWA SMA DALAM MEWUJUDKAN KESADARAN HUKUM DAN PENEGAKAN HUKUM DI SMA MUHAMMADIYAH 2 SEMARANG - Dyah Listyorini; Arikha Saputra; Fitika Andraini (Jurnal Komunikasi Hukum, 2022)
Indonesia is a state of law, therefore the law in Indonesia must be obeyed and enforced. To be able to obey and enforce the law, people must understand and understand what the law is. there are so many cases of law violations committed by high school students because they do not understand the law. This research is entitled "Application of Legal Education in High School Students in Realizing Legal Awareness and Law Enforcement in SMA Muhammadiyah 2 Semarang". Researchers in carrying out this research use a sociological juridical approach, namely by emphasizing research that aims to obtain legal knowledge empirically by going directly to the object, what is meant here is that researchers conduct direct interviews with students of Muhamadiyah 2 Semarang High School about the importance of implementing legal education in create legal awareness and law enforcement. The application of legal education is considered very important so that it can be included in school curriculum subjects as well as through legal counseling in collaboration with the relevant agencies so that students have a strong legal awareness, can distinguish between right actions and wrong actions as well as sanctions from existing law enforcement.